Custodiol-N versus Custodiol: results from a prospective noninferiority randomized single blind, multicenter phase 3 trial in patients undergoing heart transplantation - Aliabadi-Zuckermann, Arezu Z.; Osorio-Jaramillo, Emilio; Knosalla, Christoph; Gummert, Jan; Szabó, Gábor; Wittmann, Franziska; Yeter, Ruhi; Schramm, Rene; Goekler, Johannes; Hennig, Felix; Morshuis, Michel; Zuckermann, Andreas (The journal of heart and lung transplantation, 2025)
Background - Custodiol is a well-established preservation solution for organ transplantation and was the basis for the development of Custodiol-N to improve graft preservation. Previous results in coronary artery bypass graft surgery have shown effective cardiac protection without safety concerns. This study aimed to evaluate the safety and ability of Custodiol-N to preserve cardiac grafts for heart transplantation. - Methods - This prospective, randomized, single-blind, multicenter, noninferiority study was conducted at three centers in Austria and Germany. The primary end-point was creatine kinase (CK-MB) peak value from 4 to 168 hours after opening of the aortic cross clamp, with a 30% noninferiority margin. Key secondary efficacy end-points include patient and graft survival, incidence of primary graft failure, or length of stay in the intensive care unit. The primary and secondary end-points were analyzed in both the treated and per protocol populations. - Results - A total of 105 randomized patients received Custodiol (n = 52) or Custodiol-N (n = 53) preserved hearts. Average donor age and ischemic times were comparable. Average CK-MB peak values were 176.94 ± 189.61 U/L for the Custodiol versus 130.51 ± 69.60 U/liter for the Custodiol-N group (p-value for noninferiority of Custodiol-N by 30% <0.0001). Patient survival was comparable 1-year post transplantation (90.4% for Custodiol versus 88.7% for Custodiol-N). The incidence of primary graft failure and median length of intensive care unit stay were higher for Custodiol group. Safety assessment showed evenly distributed adverse events. - Conclusions - This study shows that Custodiol-N is safe, noninferior, and provides similar cardiac graft protection as the established Custodiol solution.
Online verfügbar: 23. April 2025, Artikelversion: 25. Juli 2025
Gesehen am 19.01.2026